The Efficacy of Topical Sucralfate for Skin Ulcer: A Systematic Review of Randomized Control Trials and Cohort Studies - Maharani, Sarasukma; Savira, Olivia; Indraswari, Made Ratna Savitri; Asmarajaya, Anak Agung Gde Ngurah (Jurnal Locus Penelitian dan Pengabdian, 2025)
Wound care in ulcers often poses significant challenges due to prolonged healing time and frequently unsatisfactory outcomes. The use of topical modalities to maintain a moist wound environment continues to be developed. Sucralfate, as a cytoprotective agent for gastric mucosa, has shown potential in the management of ulcers. This systematic review aims to determine the efficacy of topical sucralfate in ulcer wound healing. A comprehensive literature search was conducted across databases including PubMed and Google Scholar, for nine clinical studies published between 2008 and 2023 across multiple countries. The present study included randomized controlled trials (RCTs) and cohort studies that compared sucralfate dressing with conventional dressing. Outcomes of interest included reduction area, healing time, healing rate, and rate of granulation tissue formation. Nine studies fulfilled the eligibility criteria, assigning topical sucralfate as the intervention and conventional modalities (saline, mupirocin, povidone iodine) or placebo as comparators. The study duration ranged from 10 days to 3 months, during which topical sucralfate achieved superior outcomes, with a statistically significant reduction in healing time and greater wound area reduction compared with controls. These results indicate that topical sucralfate is effective in ulcer wound management, exerting cytoprotective effects and promoting epithelial regeneration, thereby enhancing the overall quality of wound healing. While primarily considered an adjunctive agent, the evidence demonstrates that sucralfate exerts clinically relevant effects on epithelialization and tissue recovery. Its cytoprotective properties underscore a therapeutic role that extends beyond supportive care, reinforcing its value as a complementary strategy in wound management.